Roles of thermophilic thiosulfate-reducing bacteria and methanogenic archaea in the biocorrosion of oil pipelines - Liang, Renxing; Grizzle, Robert S.; Duncan, Kathleen E.; McInerney, Michael J.; Suflita, Joseph M. (Frontiers in Microbiology, 2014)
Thermophilic sulfide-producing microorganisms from an oil pipeline network were enumerated with different sulfur oxyanions as electron acceptors at 55 oC. Most-probable number (MPN) analysis showed that thiosulfate-reducing bacteria were the most numerous sulfidogenic microorganisms in pipeline inspection gauge (PIG) scrapings. Thiosulfate-reducing and methanogenic enrichments were obtained from the MPN cultures that were able to use yeast extract as the electron donor. Molecular analysis revealed that both enrichments harbored the same dominant bacterium, which belonged to the genus Anaerobaculum. The dominant archaeon in the methanogenic enrichment was affiliated with the genus Methanothermobacter. With yeast extract as the electron donor, the general corrosion rate by the thiosulfate-reducing enrichment (8.43 ± 1.40 milli-inch per year, abbreviated as mpy) was about 5.5 times greater than the abiotic control (1.49 ± 0.15 mpy), while the comparable measures for the methanogenic culture were 2.03 ± 0.49 mpy and 0.62 ± 0.07 mpy, respectively. Total iron analysis in the cultures largely accounted for the mass loss of iron measured in the weight loss determinations. Profilometry analysis of polished steel coupons incubated in the presence of the thiosulfate-reducing enrichment revealed 59 pits over an area of 71.16 mm2, while only 6 pits were evident in the corresponding methanogenic incubations. The results show the importance of thiosulfate-utilizing, sulfide-producing fermentative bacteria such as Anaerobaculum sp. in the corrosion of carbon steel, but also suggest that Anaerobaculum sp. are of far less concern when growing syntrophically with methanogens.